Analysis Of Local Wisdom In The Discourse Of Indonesian Folklore Malin Kundang Si Anak Durhaka - Yuni Wulandari; T. Thyrhaya Zein; Eddy Setia (CV. Inara, 2021)
This study discusses the local wisdom of the folklore of the archipelago, Malin Kundang, the child of disobedience, with a text structure analysis approach. The research method used is the descriptive qualitative method. The data in this study is the text of the folklore of Malin Kundang Si Anak Durhaka (Malin Kundang the Son of Disobedience). From the results of the study, it was concluded that the analysis of the discourse aspect of the text, which was reviewed on two analytical approaches, namely linguistic analysis, and structural analysis, provided an in-depth understanding of the coherence and coherence of the text so that the contents of the text could be well understood. The socio-cultural context of Minang community life in the text includes social strata or social class, marriage customs, leadership, arts, and beliefs of the Minang community. Furthermore, the socio-cultural context in the text contributes to the life of the Minang community in creating harmony and harmony in society and state life, which is marked by the creation of (customary laws) in each village and is regulated based on local village customs. Local wisdom in the story is known, among others, the value of moral education, politeness education, the value of preserving traditional culture, identity recognition, and religious values.